Congenital heart disease in the neonate: results of surgical treatment. Issue 2 (February 1983) - Bove, E L; Bull, C; Stark, J; de Leval, M; Macartney, F J; Taylor, J F
Abstract : All 212 neonates undergoing cardiac surgery at this hospital during the 5-year period from 1976 to 1980 inclusive were reviewed. Forty required open heart surgery with 23 (57%) deaths. One hundred and seventy-four neonates underwent non-bypass procedures and could be divided into three groups: group 1 (82 patients) had inadequate pulmonary blood flow, group 2 (33 patients) had increased pulmonary blood flow or inadequate mixing, and group 3 (59 patients) had coarctation of the aorta, alone or with associated lesions. Forty-four (25%) of the neonates undergoing non-bypass procedures died. Two required bypass surgery later in the first month of life. Metabolic acidosis and the need for preoperative respiratory support were appreciably greater in non-surviving patients. The spectrum of diagnoses encountered and types of operative procedures performed are analysed.